A Challenging Case of High-Risk Pediatric AML with Novel ZNF348/SF11 Fusion and Mixed Phenotypic Features: Navigating Genomic Complexity, Resistant Infections, and MRD-Driven Therapy toward Remission - Dhandapani, C.; A, Kavitha (Indian Journal of Pharmacy Practice)
Acute Myeloid Leukemia (AML) with mixed phenotypic features represents a rare and high-risk subset of childhood leukemia. This case highlights a pediatric patient harboring a novel ZNF348/ SF11 fusion and NRAS mutation, emphasizing the diagnostic complexity, therapeutic resistance, and role of Minimal Residual Disease (MRD)-guided treatment in achieving remission. A 5-year- old male presented with fever, vomiting, petechiae, hepatosplenomegaly, and pancytopenia. Diagnostic evaluation included peripheral smear, bone marrow cytology, flow cytometry, and molecular profiling. The patient was treated with sequential chemotherapy regimens-ADE induction, FLA-B salvage, and MRD-adapted therapy using Venetoclax and Blinatumomab-along with aggressive infection control for carbapenem-resistant organisms. Initial ADE induction achieved morphologic remission but persistent MRD (19.25%). Following FLA-B and subsequent FLA-B + Venetoclax therapy, MRD declined to 0.6%. The combination of Blinatumomab and Venetoclax was initiated to achieve MRD negativity prior to allogeneic Hematopoietic Stem Cell Transplantation (HSCT). The course was complicated by multidrug-resistant infections, successfully managed through targeted antibiotic therapy and multidisciplinary care. This case underscores the clinical and genomic complexity of mixed-phenotypic AML with novel gene fusion. Persistent MRD after standard therapy necessitated precision-guided salvage regimens integrating Venetoclax and Blinatumomab. Early MRD monitoring, infection control, and timely transplant planning are critical for improving outcomes in such high-risk pediatric AML cases.
Keywords: Pediatric AML; Mixed Phenotypic Acute Leukemia; ZNF348/SF11 Fusion; NRAS; Mutation; MRD; Venetoclax; Blinatumomab; Carbapenem-Resistant Infection; Allogeneic Stem; Cell Transplantation